A study of sociodemographic determinants, reasons and decision maker of medical termination of pregnancy in urban slums of Jamnagar, India - Koringa, Hetal T.; Joshi, Krupal J.; Mehta, Jitesh P. (International Journal of Research in Medical Sciences, 2017)
Background: Medical termination of pregnancy is defined as “willful termination of pregnancy before the age of viability of the foetus. The objective was to study the socio-demographic & obstetric profile and the reasons for procuring an abortion & choice of health care provider. Methods: A Cross-sectional study was done in urban slum in Jamnagar municipal corporation area by using 30 clusters sampling technique. Every women in the reproductive age group (15-49 years) was included in the study till the sample size of 15 was completed in each cluster and thus total 450 women were interviewed. 48 women out of the total of 450 ever married women in the reproductive age group who had ever undergone induced abortion were studied in detail Results: In the present study out of 450 eligible women, 48 (10.67%) had undergone an induced abortion and once only. 72.91% (35/48) of the women belonged to the age group 25-34 years and 89.59% (43/48) of the women were Hindus. Almost half of the total women (45.83%) had primary education, higher proportion of women were housewife 77.09% (37/48). According to Modified Prasad’s classification, 54.17 % of women belonged to lower social class (IV and V). One third (33.33%) of the women who underwent MTP had 1 living child. Majority 79.16% of the women preferred government hospital and in 45.83% cases both husband and wife acted as decision maker for MTP. Most common reason given for terminating the pregnancy was “birth spacing”. (52.09%) Other reasons given were, “family completed” (22.91%), “medical” (14.58%) & social (4.17%). Majority of the women (70.83%) accepted post abortion contraception. Conclusion: There is need to counsel women of reproductive age group that MTP is not a way to control unwanted birth and it is not free from risk. They should be motivated for various methods of contraception.